1999
DOI: 10.1021/la990092+
|View full text |Cite
|
Sign up to set email alerts
|

An AFM Study of Lipid Monolayers. 1. Pressure-Induced Phase Behavior of Single and Mixed Fatty Acids

Abstract: Monolayers of palmitic (C16:0) and lignoceric acid (C24:0) and their equimolar mixture were transferred to a hydrophilic mica substrate at various surface pressures and investigated by means of atomic force microscopy (AFM) in contact and lateral force modes. The first-order transition of lignoceric acid gives a plateau region, representing a liquid expanded to liquid condensed phase transition in the pressure-area isotherm. This was visualized by AFM as stripes of a condensed phase within the expanded phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 21 publications
9
62
3
Order By: Relevance
“…When the surface pressure values of phase transitions in mixed monolayers are similar to the ones observed for the pure component monolayers, this indicates immiscibility between the two components at the air-water interface [29]. In this study, it has been shown that the surface pressure of the characteristic transition of DPPC and the surface pressure corresponding to the final plateau of fengycin monolayers are higher when these two compounds are mixed at the air-water interface.…”
Section: Interfacial Properties Of Pure Dppc and Of Mixed Dppc/fengycsupporting
confidence: 65%
“…When the surface pressure values of phase transitions in mixed monolayers are similar to the ones observed for the pure component monolayers, this indicates immiscibility between the two components at the air-water interface [29]. In this study, it has been shown that the surface pressure of the characteristic transition of DPPC and the surface pressure corresponding to the final plateau of fengycin monolayers are higher when these two compounds are mixed at the air-water interface.…”
Section: Interfacial Properties Of Pure Dppc and Of Mixed Dppc/fengycsupporting
confidence: 65%
“…3), even with further magnification. This was surprising because height differences of c. 1.5 nm have been observed for fatty acids on mica surfaces (Ekelund et al ., 1999). However, in the present case, the outer β‐layer is maintained on a softer and more uneven support.…”
Section: Resultsmentioning
confidence: 97%
“…The deposited lipid Wlm was left for 25 min for the solvent to evaporate, and thereafter compressed to 22 mN/m at a speed of 1 mN/m per minute, with a maximum barrier speed of 10 mm/min (cf. Ekelund et al, 1999;Sparr et al, 1999). Three isotherm cycles were performed to ensure reproducibility.…”
Section: Preparation Of Langmuir-blodgett Lipid Monolayer Wlmsmentioning
confidence: 99%